GEOGRAPHIC INFORMATION SYSTEM AS DETERMINATION OF STRATEGIC LOCATIONS AND SHORTEST ROUTES IN BANDUNG USING DIJKSTRA METHOD - Sari Armiati; Liane Okdinawati; Dewi Selviani Yulientinah (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2010)
Banding is one of the cities which is always visited by a huge number of tourists. The frequency of the visitincreases every year. This city has a large number tourism objects and strategic places to visit. Therefore, it isessential to design an information-based technology application which can make finding strategic places inBandung easier and can give information of shortest routes from origin places to the destinations. The users ofthis application will include administrator and public visitor. The administrator will enter the data of places,weight, place types and other strategic location attributes. Public visitors will be able to see the map display andcan enter the origin places and destinations. The output of the application which will be built in the second yearis the shortest route display which is based on the inputs from both users.The research is first year competitivegrant research which is funded by Higher Education Office (Dikti) in 2009. This research involves threeresearchers, ten students and one administration staff. In the first year, the research emphasizes on analyticaland designing phase by using structured method, that is by applying Dijkstra Method in the algorithm of shortestroute searching. Functions prepared in this information system is designed by using modeling tools likestructure chart, menu structure, Data Flow Diagram (DFD) as modeling process explained in processspecification and Entity Relationship (ER) as data modeling. Apart from that, this design is equipped with testingdesign which will be conducted after the information system is built in the second year of the research.Key Words: Geographic Information System, Bandung, Shortest Routes, Dijkstra Method